2020
DOI: 10.1007/s00392-020-01703-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 outbreak on regional STEMI care in Germany

Abstract: Aims To assess the impact of the lockdown due to coronavirus disease 2019 (COVID-19) on key quality indicators for the treatment of ST-segment elevation myocardial infarction (STEMI) patients. Methods Data were obtained from 41 hospitals participating in the prospective Feedback Intervention and Treatment Times in ST-Elevation Myocardial Infarction (FITT-STEMI) study, including 15,800 patients treated for acute STEMI from January 2017 to the end of March 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
2
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 28 publications
7
57
2
13
Order By: Relevance
“…In the case of ST-elevation myocardial infarction (STEMI) with suspected COVID-19, the protocol dictates immediate cardiac catheterization in a dedicated catheter laboratory with all protective measures in place, including proper negative pressure room ventilation and personal protective devices such as FFP‑3 face masks, in accordance with guidelines of the German Society of Cardiology [ 13 ]. With regard to door-to-balloon intervals, a possible delay in care delivery has been observed in the current literature [ 5 ], while other studies showed no significant delay in ACS management throughout the STEMI Network in Germany, and as the authorsʼ managing protocols did not change during the outbreak, they do not expect a significant delay to have taken place in their hospital [ 2 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the case of ST-elevation myocardial infarction (STEMI) with suspected COVID-19, the protocol dictates immediate cardiac catheterization in a dedicated catheter laboratory with all protective measures in place, including proper negative pressure room ventilation and personal protective devices such as FFP‑3 face masks, in accordance with guidelines of the German Society of Cardiology [ 13 ]. With regard to door-to-balloon intervals, a possible delay in care delivery has been observed in the current literature [ 5 ], while other studies showed no significant delay in ACS management throughout the STEMI Network in Germany, and as the authorsʼ managing protocols did not change during the outbreak, they do not expect a significant delay to have taken place in their hospital [ 2 ].…”
Section: Discussionsupporting
confidence: 88%
“…[13]. With regard to door-to-balloon intervals, a possible delay in care delivery has been observed in the current literature [5], while other studies showed no significant delay in ACS management throughout the STEMI Network in Germany, and as the authors' managing protocols did not change during the outbreak, they do not expect a significant delay to have taken place in their hospital [2].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Instead, secondary effects that are not directly related to COVID-19 disease such as misinterpretation of symptoms (dyspnea and chest discomfort rather interpreted as sign of respiratory disease by the patient), strict instructions to stay at home, and increased fear of patients to contact SARS-CoV-2 in medical facilities as a consequence of RM and of the impact of the pandemic situation on individual decision making may be responsible for delayed contact with health care professionals. Of note, the authors of an analysis of the FITT-STEMI trial reported that pre-clinical logistic structures, including contact-to-ballon times, were preserved during the COVID-19 pandemic in Germany, supporting the concept that delayed admissions may indeed result from hesitation to contact the medical system [ 23 ]. Avoiding health care may similarly be the reason for less new diagnoses of cancer in the Netherlands since the onset of the COVID-19 pandemic, thereby likely delaying timely therapeutic intervention and also impairing prognosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…hesitation to contact the medical system [23]. Avoiding health care may similarly be the reason for less new diagnoses of cancer in the Netherlands since the onset of the COVID-19 pandemic, thereby likely delaying timely therapeutic intervention and also impairing prognosis [24].…”
Section: Plos Onementioning
confidence: 99%